Micro mechanics of critical states for isotropically overconsolidated sand - McDowell, Glenn R.; Yue, Peng; de Bono, John P. (Elsevier, 2015)
The discrete element method has been used to investigate the micro mechanics of shearing to a critical state on the loose and dense sides of critical. Isotropic compression has previously been modelled in 3D using a large number of particles and without the use of agglomerates. The same procedure is used here. Particle fracture is governed by the octahedral shear stress within the particle due to the multiple contacts and a Weibull distribution of strengths. Isotropic compression of a silica sand has been simulated to 20 MPa and followed by unloading to a range of stresses before shearing to a critical state, using micro parameters which relate to the silica sand particle strengths. The samples at the lowest stress levels exhibit peak strength and dilation. The sample at the highest stress exhibits contraction and ductile yielding to a critical state. A critical state line is established, which appears to become parallel to the isotropic line in log e-log p space at high stress levels. This paper shows that it is the evolving fractal particle size distribution during isotropic normal compression which governs the behaviour on unloading to different overconsolidation ratios. The micro mechanics of the critical state line are shown to be in the evolving particle size distribution during normal compression, and how such an aggregate behaves when it is unloaded.